Proposing a New MAC Layer Schedule with the Aim of Reducing Energy Consumption in Wireless Sensor Networks - Farhad Mesrinejad; Hassan Aliahmadi (Majlesi Journal of Electrical Engineering)
Recent advances in the field of electronics and wireless telecommunications have created the capability and potential for designing and manufacturing sensors which have low power consumption, small size, reasonable price and various applications. These small sensors, which based on their type, can perform different tasks such as receiving environmental information, processing it and then sending that information, have shaped an idea to create and expand networks known as wireless sensor network (WSN). A sensor network consists of a large number of sensor nodes which are widely distributed in the environment and are engaged in collecting information. The sensors have significant limitations, and one of the most important limitations is the low capacity of these sensorsâ battery, which makes the efficient use of the energy a vital issue. When the energy in the battery ends, the sensorâs functions completely stops. This would result in the loss of a part of the network. Moreover, in most of the sensorâs applications, replacing the battery is impossible either because the evaluated area is too large or because it is unsafe. Therefore, minimizing the energy consumption, by designing communication protocols and applications for these networks, is one of the most important issues. So designing a MAC Layer schedule to reduce energy consumption in wireless sensor networks which can significantly reduce power consumption but also would be compatible with IEEE 802.15.4 is an important and unavoidable challenge.